The effects of labels on teacher expectancy - Adorio, Mercedes P.
The purpose of this study was to determine (1) the extent to which subjects have negative stereotype expectations regarding emotionally disturbed children, and (2) the extent to which these stereotypes are maintained in the face of conflicting situation. The subjects were 29 graduate students enrolled in special education program of a university. They were enrolled in an introductory course in special education and psychology of exceptional children, two general courses which introduce the study of learning and behavior characteristics of emotionally disturbed children.
Keywords: Emotional problems of children; Emotional disorders in children; Behavior disorders in children; Special education